Micro-patterns of violence: disaggregating Provisional Irish Republican Army activity, 1969-1979 - Kowalski, RC (2023)
This thesis examines the first ten years of the campaign of political violence that was waged by the Provisional Irish Republican Army (PIRA) during the Northern Ireland Troubles (c.1969–1998). The primary aim is to understand how and why the PIRA chose to apply violence, and the consequences of these decisions. What is significant about this thesis, is the volume and range of PIRA violence that has been disaggregated and assessed – fatal and non-fatal acts of violence; targeted assassinations that were planned and executed as intended; operations that were stillborn, off-target, or thwarted by the security forces; attacks that maimed or killed unintended targets; and acts that were never intended to and did not cause physical harm to others. The work uncovers a richer account of the relationship between PIRA agency, chance, and the character and consequences of PIRA violence than has hitherto been possible.